Intermediate financial management - Brigham, Eugene F. (Canada : South-Western Cengage Learning, 2013)
This book provides a balance of theory and practical applications to help you understand the financial problems facing businesses and the best solutions.
Part I. Fundamental Concepts of Corporate Finance -- Part II. Corporate Valuation -- Part III. Project Valuation -- Part IV. Strategic Financing Decisions -- Part V. Tactical Financing Decisions -- Part VI. Working Capital Management -- Part VII. Special Topics .
Includes index.
Keywords: BUSINESS ENTERPRISES